2020
DOI: 10.1111/1753-0407.13089
|View full text |Cite
|
Sign up to set email alerts
|

Low serum levels of bone turnover markers are associated with the presence and severity of diabetic retinopathy in patients with type 2 diabetes mellitus

Abstract: Background: Accumulating evidence demonstrates an association of type 2 diabetes mellitus (T2DM) and its microvascular complications with increased fracture risk. In this study, we aimed to evaluate the relationships between serum concentrations of bone turnover markers and the presence and/or severity of diabetic retinopathy (DR) among patients with T2DM. Methods: A total of 285 patients with T2DM comprising 168 patients without DR and 117 patients with DR were enrolled in the cross-sectional study. In the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
(110 reference statements)
0
12
0
Order By: Relevance
“…Serum bone turnover markers can be used to assess bone loss or formation more sensitive than BMD ( 53 55 ). Previous studies demonstrated reduced bone resorption and formation in T2D individuals ( 56 58 ), suggesting that hyperglycemia and AGEs crosslinking may impair the function of osteoblasts and osteoclasts, thereby inhibiting bone formation and promoting bone resorption. Correlation analysis in our study also confirmed the AGEs level was positively correlated with glycemic parameters including FBG, HbA1c, HOMA-IR, bone resorption marker S-CTX, and negatively correlated with bone formation marker PINP in postmenopausal T2D patients.…”
Section: Discussionmentioning
confidence: 96%
“…Serum bone turnover markers can be used to assess bone loss or formation more sensitive than BMD ( 53 55 ). Previous studies demonstrated reduced bone resorption and formation in T2D individuals ( 56 58 ), suggesting that hyperglycemia and AGEs crosslinking may impair the function of osteoblasts and osteoclasts, thereby inhibiting bone formation and promoting bone resorption. Correlation analysis in our study also confirmed the AGEs level was positively correlated with glycemic parameters including FBG, HbA1c, HOMA-IR, bone resorption marker S-CTX, and negatively correlated with bone formation marker PINP in postmenopausal T2D patients.…”
Section: Discussionmentioning
confidence: 96%
“…After adjusting these factors, our results were similar to those of previous studies. An et al 49 found that serum OC and β-CTX levels were significantly lower among 117 patients with DR than among 168 patients without DR. However, they observed that serum P1NP and β-CTX levels were inversely associated with DR risk, which was different from our results.…”
Section: Discussionmentioning
confidence: 99%
“…The close interaction between bone and other organ, including CNS is a research hotspot in recent years [ 27 ]. Bone is emerging as a multi-faceted endocrine organ by secreting several osteokines including OCN [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%